Unveiling the Colours of Cellulose Nitrate Black and White Film-based Negatives in Colonial Photography - Roldão, Élia (2022)
ERDF/PT2020/POCI-01-0145-FEDER-007265; Project - PTDC/IVC-HFC/5174/2014; NEMOSINE project by European Union (EU)